Covalently linked polydopamine-modified boron nitride nanosheets/polyimide composite fibers with enhanced heat diffusion and mechanical behaviors. (15th October 2020) - Fang, Yuting; Dong, Jie; Zhao, Xin; Chen, Tongtong; Xiang, Liping; Xie, Yangsu; Zhang, Qinghua
Abstract: Polymer fibers with high tensile strength and high thermal conductivity ( k ) are attractive in next-generation thermoregulating textiles, wearable electronic devices and so on. However, most polymeric fibers usually have a low thermal conductivity below 0.5 W m −1 K −1, hardly satisfying the high requirements for thermal management. Herein, we report an effective approach to achieve a highly thermally conductive and high-strength polyimide (PI) composite fibers containing the polydopamine modified boron nitride nanosheets (PDA@BNNS). The uniform dispersion of nanofiller, covalent adhesion of PDA@BNNS to PI matrix and highly aligned PDA@BNNS network are successfully realized during in-situ polymerization, wet-spinning and post hot-drawing process. Thus, significant improvements in the heat diffusion behavior and mechanical property for PI/PDA@BNNS composite fibers are achieved. The incorporation of a very low content of PDA@BNNS ( 0.5 wt%) results in a 27% increase in thermal conductivity for the PI/PDA@BNNS-0.5 composite fiber. An optimum thermal conductivity of 3.44 W m −1 K −1 for the composite fiber is obtained with 10 wt% nanofiller addition, and meanwhile, the tensile strength and modulus approach 1.8 GPa and 100.7 GPa, respectively, far exceeding most of the BNNS containing composite fibers. Additionally, these composite fibers are scalable and weavable, making them good candidates for the future advanced functional textiles or as the reinforcement in thermally conductive composites applications. Graphical abstract: Image 1 Highlights: Polyimide-based composite fiber containing PDA-modified BNNS was prepared. Covalent bonding of BNNS and polyimide creates a strong interfacial interaction. Fiber processing facilitates the oriented distribution of BNNS in composite fiber. Mechanical properties of the fibers surpass most of existing BNNS containing fibers. The composite fiber has a sufficiently high thermal conductivity of 3.44 W m −1 K −1 .